The Effect of Compensation And Motivation on Employee Performance At The Palopo City Land Office - Reckza Pujangga; Kusdarianto, Indra; Halim, Ibrahim (LP2M IAIN Palopo, 2025)
This study was conducted to analyze the effect of compensation and work motivation on employee performance at the Palopo City Land Office.The approach used is a quantitative research method with a descriptive and analytical design. The research sample includes all employees in the office, totaling 47 people. Data were collected through a questionnaire that had been tested for validity, and the data were analyzed using multiple linear regression with the help of SPSS software. The results of the study revealed that work discipline and work motivation, both individually and simultaneously, have a positive and significant effect on employee performance.